Validation of iGPS as an external measurement system for cooperative robot positioning - Norman, Andrew R.; Schönberg, Alexander; Gorlach, Igor A.; Schmitt, Robert (International journal of advanced manufacturing technology, 2013)
External metrology systems are increasingly being used in modern manufacturing to improve the accuracy of industrial robots. In this paper, the problem of achieving absolute accuracy in the positioning and movement of cooperating robots is addressed using the indoor GPS (iGPS) technology as an external position measurement system for real-time feedback and control. This metrology system is presented as an introduction to the iGPS-based 3D Pose Detector and a new concept using generalised measurement systems inspired by iGPS. Attached to the robot end-effectors, the receivers allow coordinate frame measurements to provide spatial information on the robot poses in six degrees of freedom. Experimental results show a strong correspondence between iGPS measurements of cooperating robot end-effector positioning and the control measurements obtained from a double ballbar. Ballbar measurements are further used to determine the relative accuracy between state-of-the-art cooperating manipulators. The iGPS system is validated as an external measurement system using a ballbar device, and its use in the external control of basic robotic tasks is demonstrated. The predicted accuracy achievable for the robots when being controlled or compensated is determined to be at least within 0.3 mm, subject to improvements with continuing research and refinements.